Alternative products with insecticidal effect in the control of Aulacaspis tubercularis; Newstead, 1906 (Hemiptera: Diaspididae) in mango cultivation - Ramos , Yaneth; Valverde-Rodríguez, Agustina; Cornejo, Antonio; Jara, Fleli (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
The predominant microclimates of the coast and the inter-Andean valleys of Peru have favored the production and export of mango (Mangifera indica L.) to more than 30 countries in the years 2020 - 2021. In this process, phytosanitary support was of vital importance, however, the species Aulacaspis tubercularis Newstead, 1906 (Hemiptera: Diaspididae) is a pest that affects the resulting crop, increasing costs due to cleaning the fruits for marketing. Control with insecticides contaminates the environment; hence the objective of the study was to evaluate alternative products with insecticidal effect and low environmental impact. The use of mineral oil (7.5 mL.L-1), azadirachtin (3.2 %, 5 mL.L-1), commercial powder detergent (20 g.L-1) and potassium soap (10 mL.L-1) in the field and laboratory. In the field, 9 trees were sprayed per treatment, every seven days at an interval of 15 days and in the laboratory the individuals per bottle. The four evaluated products had a significant impact on the colonies in the field (95.31 %, 88.89 %, 77.38 % and 68.04 %, respectively) in the first three moments of application. In the laboratory, commercial detergent and 3.2 % azadirachtin exerted high mortality (100 %) on the third day post-application, followed by 100 % mineral oil on the fourth day. The four products evaluated are recommended for the management of A. tubercularis.